2011
DOI: 10.2337/dc10-1905
|View full text |Cite
|
Sign up to set email alerts
|

A New-Generation Ultra-Long-Acting Basal Insulin With a Bolus Boost Compared With Insulin Glargine in Insulin-Naïve People With Type 2 Diabetes

Abstract: OBJECTIVEInsulin degludec/insulin aspart (IDegAsp) is a soluble coformulation of the novel basal analog insulin degludec (IDeg: 70%) and insulin aspart (IAsp: 30%). We compared the safety and efficacy of IDegAsp, an alternative formulation (AF) (55% IDeg and 45% IAsp), and insulin glargine (IGlar) in insulin-naïve subjects with type 2 diabetes inadequately controlled with oral antidiabetic drugs.RESEARCH DESIGN AND METHODSIn this 16-week, open-label trial, subjects (mean age 59.1 years, A1C 8.5%, BMI 30.3 kg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 18 publications
4
122
0
3
Order By: Relevance
“…8 Briefly, patients were included if they were insulin-naïve adults (18-75 years of age) with type 2 diabetes, had HbA1c of 7-11% and body mass index of 25-37 kg/m 2 , and were treated with up to two oral antidiabetic drugs (OADs; excluding thiazolidinediones) in the 2 months prior to trial at stable maximum doses or at least half maximum allowed doses. Fuller details on the inclusion and exclusion criteria have been reported previously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Briefly, patients were included if they were insulin-naïve adults (18-75 years of age) with type 2 diabetes, had HbA1c of 7-11% and body mass index of 25-37 kg/m 2 , and were treated with up to two oral antidiabetic drugs (OADs; excluding thiazolidinediones) in the 2 months prior to trial at stable maximum doses or at least half maximum allowed doses. Fuller details on the inclusion and exclusion criteria have been reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…Fuller details on the inclusion and exclusion criteria have been reported previously. 8 The patients were randomized in a 1:1:1 ratio to add a once-daily evening injection of IDegAsp, IGlar, or an alternative formulation of IDeg/IAsp. Except for metformin, all OADs were discontinued.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“….0% vs. IGlar: 7.1%), but with better dinner-time postprandial glycemic control and lower rates of hypoglycemia [41]. The trend of lower hypoglycemia rates in phase 2 trials was later observed in phase 3 trials (Table 2).…”
Section: Phase 2 Clinical Trialsmentioning
confidence: 84%
“…Due to its lesser day-to-day variability, degludec has the potential to further reduce the risk of hypoglycaemia than other long-acting basal insulins [9]. The DEVOTE study showed that degludec was non-inferior to glargine with respect to incidence of cardiovascular events with significant reductions in severe hypoglycaemia, especially nocturnal [10].…”
Section: Basal Insulin and Dose Titrationmentioning
confidence: 88%